2019
DOI: 10.3389/fsurg.2019.00065
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options for Abdominal Rectus Diastasis

Abstract: Background: Abdominal rectus diastasis is a condition where the abdominal muscles are separated by an abnormal distance due to widening of the linea alba causing the abdominal content to bulge. It is commonly acquired in pregnancies and with larger weight gains. Even though many patients suffer from the condition, treatment options are poorly investigated including the effect of physiotherapy and surgical treatment. The symptoms include pain and discomfort in the abdomen, musculoskeletal and urogynecological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 38 publications
(102 reference statements)
2
46
0
1
Order By: Relevance
“…79 Most frequently, rectus diastasis presents as a centrally located epigastric bulge in a patient with a history of truncal obesity or pregnancy; however, patients can present with abdominal pain or discomfort, back pain, or urogynecological symptoms in rare cases. 79,80 Plication of the rectus sheath is the gold standard treatment for rectus diastasis. There are several techniques that may be employed for rectus diastasis repair, though plastic surgeons typically use an open approach (via abdominoplasty) and plicate the anterior rectus sheath.…”
Section: Lower Trunkmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Most frequently, rectus diastasis presents as a centrally located epigastric bulge in a patient with a history of truncal obesity or pregnancy; however, patients can present with abdominal pain or discomfort, back pain, or urogynecological symptoms in rare cases. 79,80 Plication of the rectus sheath is the gold standard treatment for rectus diastasis. There are several techniques that may be employed for rectus diastasis repair, though plastic surgeons typically use an open approach (via abdominoplasty) and plicate the anterior rectus sheath.…”
Section: Lower Trunkmentioning
confidence: 99%
“…Recurrence of rectus diastasis is uncommon following plication, with studies reporting recurrence in only 0% to 4% of patients. [80][81][82]…”
Section: Lower Trunkmentioning
confidence: 99%
“…Details of strength and functional outcome scales can be found in Table 3 . Objective and subjective measurements of abdominal strength were reported in three studies, and the details of each study can be found in Table 4 [ 1 , 18 , 20 ]. Overall, rectus plication did not consistently improve abdominal strength.…”
Section: Reviewmentioning
confidence: 99%
“…Abdominal rectus diastasis (ARD) is the separation of the rectus muscles due to thinning along the linea alba [ 1 ]. This separation may be caused by abdominal obesity, pregnancy, or congenital collagen abnormalities, and can lead to a permanent increase in the width of the aponeuroses from the patient's baseline by several centimetres [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plication-based techniques include open plication, laparoscopic plication, or hybrid plication of either the anterior or posterior rectus fascia. Plication can be performed with single-or double-layer sutures, using an interrupted or continuous, absorbable, slowly absorbable, or permanent sutures according to the surgeon's preferences [2][3][4]. In the case of coexistence of extensive laxity of the abdominal wall, onlay mesh reinforcement is generally used, even though there is a lack of evidence on which type of mesh should be used.…”
mentioning
confidence: 99%